Resumos Do... 2019
DOI: 10.20396/revpibic2720192866
|View full text |Cite
|
Sign up to set email alerts
|

Produção de biogás a partir de vinhaça de 1ª e 2ª geração e licor de pentoses utilizando planejamento experimental e metodologia de superfície de resposta

Abstract: ResumoAplicação das correntes líquidas residuárias da biorrefinaria de cana-de-açúcar (1G2G) na digestão anaeróbia visando a produção de biogás e, consequentemente, bioenergia. A codigestão desses resíduos orgânicos possibilita melhorar o rendimento de metano e reduzir potenciais efeitos inibitórios de determinados resíduos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results showed that the mixture mentioned boosted CH 4 generation (568 Nl CH 4. g VS ‐1 ) compared to isolated substrates. The main gains achieved with pentose liquor and vinasse 1G were 12.7% and 15.4% higher than individually, respectively 18 …”
Section: Background Of Co‐substrates For Energy Purposesmentioning
confidence: 79%
See 1 more Smart Citation
“…The results showed that the mixture mentioned boosted CH 4 generation (568 Nl CH 4. g VS ‐1 ) compared to isolated substrates. The main gains achieved with pentose liquor and vinasse 1G were 12.7% and 15.4% higher than individually, respectively 18 …”
Section: Background Of Co‐substrates For Energy Purposesmentioning
confidence: 79%
“…The main gains achieved with pentose liquor and vinasse 1G were 12.7% and 15.4% higher than individually, respectively. 18 Other survey showed that combining swine manure and sugarcane vinasse in different proportions of total solids (TS) resulted in higher yield compared to vinasse-straw. The hydrogenotrophic methanogenesis pathway is not carried out appropriately in some unknown proportions of swine manure, most likely due to the high nitrogen content in the form of ammonia, which can inhibit CH 4 conversion.…”
Section: Background Of Co-substrates For Energy Purposesmentioning
confidence: 99%
“…To quote, the application of vinasse for irrigation is only considered because it contains inorganic compounds, particularly potassium (K), an important nutrient for soil fertilization (Lucas Tadeu Fuess, 2017). The high organic matter content indicates its potential AD substrate (Lima, 2020;Moraes et al, 2014). The literature cites the large volume of vinasse that is generated but does not deeply discuss the correct control of the applied organic load rate (OLR) when feeding a biodigester, since the large water volume in the composition can change the organic content fed into the reactor at each batch.…”
Section: Sugarcane Sectormentioning
confidence: 99%